2023
DOI: 10.31083/j.fbl2802023
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ganoderma lucidum Spore Powder on Acute Liver Injury in Mice and its Regulation of Gut Microbiota

Abstract: Background: Ganoderma lucidum spore powder (GLSP) has abundant pharmacological activities. However, the difference in the hepatoprotective function of sporoderm-broken and sporoderm-unbroken Ganoderma spore powder has not been studied. This study is the first to investigate the effects of both sporoderm-damaged and sporoderm-intact GLSP on the improvement of acute alcoholic liver injury in mice and gut microbiota of mice. Methods: Serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(46 reference statements)
0
1
0
Order By: Relevance
“… Jiang et al (2021a) in vitro fermentation of black G. lucidum polysaccharide (PSG) effectively improves the gut flora disorder in SD rats with acrylamide (AA)-induced liver injury, by increasing the relative abundance of Ruminococcus and Lactobacillus and reducing Prevotella It is a relative abundance, thereby achieving the liver protective effect. The edible G. lucidum spore powder (GLSP) produced by Leng et al (2023) effectively improves alcoholic liver damage (ALD) induced by 50% ethanol. GLSP can not only reduce the levels of serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) increased by ALD, but also regulate aminotransferase to improve ALD and restore intestinal health.…”
Section: Effects Of Different Components Of Ganoderma Lucid...mentioning
confidence: 99%
“… Jiang et al (2021a) in vitro fermentation of black G. lucidum polysaccharide (PSG) effectively improves the gut flora disorder in SD rats with acrylamide (AA)-induced liver injury, by increasing the relative abundance of Ruminococcus and Lactobacillus and reducing Prevotella It is a relative abundance, thereby achieving the liver protective effect. The edible G. lucidum spore powder (GLSP) produced by Leng et al (2023) effectively improves alcoholic liver damage (ALD) induced by 50% ethanol. GLSP can not only reduce the levels of serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) increased by ALD, but also regulate aminotransferase to improve ALD and restore intestinal health.…”
Section: Effects Of Different Components Of Ganoderma Lucid...mentioning
confidence: 99%
“…These triterpenoids' hepatoprotective mode of action has also been proven [37,38]. Different formulas of G. lucidum, such as spore oil, sporoderm-breaking spores and spore powder have proven to be effective against hepatic ailments [15,[39][40][41]. Various triterpenoids isolated from G. lucidum can be seen in Figure 1.…”
Section: Nutritional and Bioactive Constituentsmentioning
confidence: 99%
“…The term "liver diseases" is used to describe a broad range of illnesses that prevent or impair the liver's ability to operate. Recent studies have found that G. lucidum has a variety of hepatoprotective effects on liver illnesses, including alcoholic liver disease [15], viral hepatitis [16], NAFLD [4], fibrosis [17], hepatic cancer [8], CCl4 and amanitin-induced liver injury, etc. [18].…”
Section: Introductionmentioning
confidence: 99%